TRANSFORMATION OF MANAGERIAL LEADERSHIP QUALITIES UNDER THE INFLUENCE OF BUSINESS DIGITALIZATION - Andrii Ishchuk (Agora International Journal of Economical Sciences (AIJES), 2024)
The paper deals with identifying the directions and content of transformational changes in the leadership qualities of a manager under the influence of business digitalization. The paper aims to formulate and disclose scientific, theoretical, and methodological provisions for changing the qualities of a leader in the era of business digitalization. This study is based on observing how managers' leadership qualities are formed and developed in the context of digitalization at both global and micro levels. Identified are the differences between the characteristics of "traditional" and "digital" leaders based on historical and comparative analysis. A set of "traditional" leadership qualities allows for operational guidance and management of the company's future development based on the extrapolation of existing trends. Moreover, possession of the qualities of digital leaders enables multidimensional strategic management. The findings emphasize the importance of digital leadership at both macro and micro levels. The study shows the transformation of leadership and leadership qualities at different levels of economic management, which complements the existing scientific theories of leadership. To promote digital leadership at the macro level, the government is responsible for introducing digital technologies in administration, providing citizens with convenient tools for accessing administrative services. It was established that Ukraine is among the leading countries introducing digital technologies at the macro level. At the level of business management within companies, leadership in the digital era acquires specific characteristics compared to its traditional forms. In particular, the transition from individual to shared leadership leads to changes in organizational structures and management styles.
Keywords: 330